Evaluation of Soil Streptomyces Isolates from North-Western Ethiopia as Potential Inhibitors against Spoilage and Foodborne Bacterial Pathogens. (6th April 2022) - Girma, Abayeneh; Aemiro, Aleka
Abstract : The outbreak and spread of foodborne diseases is a serious concern for global healthcare and security. Finding novel antimicrobial agents with diverse mechanisms of action against the current spoilage and foodborne bacterial pathogens is a central strategy to overcome the problems of antibiotic resistance. Soil actinomycetes are the major antimicrobial producers with great biopreservative and medical value. This study was aimed at isolating Streptomyces from soil samples of northwestern Ethiopia against spoilage and foodborne bacterial pathogens. Thirty-six soil samples were collected at a depth of 5–10 cm in the rhizosphere and agricultural soils of soybean. A total of 118 actinomycete strains were isolated and screened primarily using the perpendicular streak plate method against 3 Gram-positive and 3 Gram-negative bacterial strains. Out of 118 isolates, 36/118 (30.50%) were active against at least two of the tested bacteria, of which 8 isolates were selected for their wide-spectrum antibacterial activities. During the disc diffusion assay, the eight in vitro ethyl acetate extract antibacterial activities range from 7 to 24 mm. The minimum inhibitory concentration and minimum bactericidal concentration values range from 0.10 to 0.25  μ g/mL and 0.15 to 0.40  μ g/mL, respectively. Following the morphological, physiological, biochemical, and molecular characteristics, eight potent isolates were identified as follows: Streptomyces fasciculus, Streptomyces roseochromogenes, Streptomyces ruber, Streptomyces glaucus, Streptomyces griseus, Streptomyces cellulosae, Streptomyces griseoflavus, and Streptomyces xanthophaeus . After the treatment of potent Streptomyces cell-free culture supernatant with proteinase K, papain, α -amylase, and lysozyme enzymes, their antagonistic effects were also observed. Most Streptomyces cell-free culture supernatant antibacterial activity was highly resistant to heat, acidity, organic solvents, and additives. Thus, the results of this investigation revealed that soil actinomycetes could be a valuable source for novel antibacterial agents applicable in food biopreservation and the treatment of spoilage and foodborne bacterial pathogens.